Low temperature electronics : physics, devices, circuits, and applications - Gutierrez-D., Edmundo A. (Academic Press, 2001)
Summarizes the advances in cryoelectronics starting from the fundamentals in physics and semiconductor devices to electronic systems, hybrid superconductor-semiconductor technologies, photonic devices, cryocoolers and thermal management. This book provides an exploration of the theory, research, and technologies related to cryoelectronics.